Comparison of electrocardiographic components in Hy Line brown hens at 70 and 90 weeks of age (2018)
In order to characterize the sympathovagal balance at different stages of life, 2 groups (70 vs 90 weeks old) of 24 clinically healthy Hy Line brown were subject to an electrocardiography (ECG) test. The ECG records were made with Power Lab 26T, using Lab